The The Dynamics of Forgiveness and Its Impact on Adolescents' Mental Health: A Qualitative Study - Irvan Usman (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
This study investigated forgiveness dynamics among adolescents in managing interpersonal conflicts both social media and within family settings, their impact on mental health. Using a phenomenological approach, semi-structured interviews were conducted with 15 adolescents aged 13–18 years in Gorontalo City, selected purposively based on their significant conflict experiences. Data were analyzed using Interpretative Phenomenological Analysis (IPA) through NVivo software to identify themes and sub-themes from their narratives. The findings highlighted forgiveness as a vital conflict resolution mechanism, particularly in mitigating the effects of conflicts stemming from social media and family disputes. Key themes included the detrimental impact of cyberbullying on mental health, forgiveness as a coping strategy to address emotional harm caused by online conflicts, and the role of forgiveness in improving family relationships. Social support and self-awareness were identified as crucial factors shaping adolescents' ability to forgive. This study fills a gap in the literature by exploring forgiveness within the dual contexts of social media and family, rarely examined together. It underscores forgiveness as a protective factor that mediates the emotional toll of conflicts, offering novel insights into adolescent mental health. The findings support the development of interventions promoting forgiveness to enhance emotional resilience and recommend further research to strengthen forgiveness as a pathway to improved adolescent well-being.